1999
DOI: 10.1046/j.1365-2435.1999.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable coexistence of contrasted nitrification statuses in a wet tropical savanna ecosystem

Abstract: Summary 1.Wet tropical savannas are characterized by strong environmental constraints-particularly low soil nutrient availability-associated with high plant productivity. Nitrogen recycling, and especially nitrification, is supposed to be a strong determinant of the balance between conservation and loss of nutrients at the ecosystem level. Savanna facies dominated by the grass Hyparrhenia diplandra (Andropogoneae) are known to exhibit low levels of nitrification and thus avoid nitrate losses. 2. By comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 32 publications
6
71
0
3
Order By: Relevance
“…The results of the current study confirm studies from Lata et al (1999Lata et al ( , 2000Lata et al ( , 2004 on natural and semi-natural vegetation, and enlarge the view that not only crop plant species can exude BNI (Subbarao et al 2007a, b;Zakir et al 2008). As was shown by Subbarao et al (2006Subbarao et al ( , 2007cSubbarao et al ( , 2009a exudates from the roots of the grass species Brachiaria humidicola and Leymus racemosus were able to influence the activity of nitrifying bacteria.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the current study confirm studies from Lata et al (1999Lata et al ( , 2000Lata et al ( , 2004 on natural and semi-natural vegetation, and enlarge the view that not only crop plant species can exude BNI (Subbarao et al 2007a, b;Zakir et al 2008). As was shown by Subbarao et al (2006Subbarao et al ( , 2007cSubbarao et al ( , 2009a exudates from the roots of the grass species Brachiaria humidicola and Leymus racemosus were able to influence the activity of nitrifying bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…Zakir et al (2008) found an increasing effect of ammonium and plant age on the release of nitrification-inhibiting compounds from the roots of Sorgum bicolor. Lata et al (1999) discovered a strong correlation between the variation in potential nitrification rate and the characteristics of nitrogen nutrition of grasses in savannas. Mature grassland systems have the ability to inhibit nitrification or have a balanced inhibition-stimulation impact (Lata et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BNI function in plants thus can exert a positive influence on NUE agronomic by reducing N loss associated with nitrification-denitrification 2013b). Recent modeling studies suggest that tropical grasses that inhibit nitrification exhibit a twofold greater productivity than those that lack such ability (Lata et al, 1999;Boudsocq et al, 2009 and.…”
Section: Biological Nitrification Inhibition (Bni)mentioning
confidence: 99%
“…A grande variação e o baixo aproveitamento podem estar relacionados as perdas do N no sistema solo-planta. Essas perdas são oriundas dos processos de lixiviação do nitrato (NO3 -) que deixa a região de exploração das raízes das plantas (OLIVEIRA et al, 1999), podendo ser perdido para atmosfera através do processo desnitrificação em condições de baixo suprimento de oxigênio (PIERZYNSKI et al, 2000), volatilização da amônia (NH3) , e perdas gasosas de nitrogênio (N2O) pelo solo (CERRI et al, 2011) e pela parte aérea das plantas Algumas plantas são capazes de inibir a nitrificação (LATA et al, 1999; . No Brasil, inúmeros trabalhos têm relacionado o cultivo ou a ocorrência de Brachiaria sp à predominância de N na forma amoniacal (CARMO et al, 2005;FERNANDES et al, 2011).…”
Section: Introductionunclassified